2019
DOI: 10.1007/s13566-020-00413-3
|View full text |Cite
|
Sign up to set email alerts
|

The value of prostate-specific antigen monitoring during salvage radiotherapy: a retrospective study and systematic review with meta-analysis

Abstract: Objective Use of salvage radiotherapy (SRT) after cancer surgery has a low disease control rate. Low prostate-specific antigen (PSA) levels in the blood pre-SRT seem to be the best predictor of success. Our study used PSA monitoring during and after treatment to investigate if PSA levels during SRT can give further information about its chances of success. Methods In a retrospective cohort of 78 patients submitted to salvage radiotherapy (SRT) for biochemical relapse after cancer surgery, we assess PSA values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The results of our study examining patients with a decline in PSA levels during salvage RT were consistent with those of previously reported studies, showing that a decrease of 0.2 or more in PSA levels during irradiation affects BR [ 20 ]. However, our results contradicted those of previous studies showing BR to be affected by decreases in PSA levels after radiation doses reached and exceeded 45 Gy [ 5 , 12 , 13 , 20 ]. In fact, our results revealed no evidence of BR in patients in whom PSA levels declined relatively early after the initiation of RT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study examining patients with a decline in PSA levels during salvage RT were consistent with those of previously reported studies, showing that a decrease of 0.2 or more in PSA levels during irradiation affects BR [ 20 ]. However, our results contradicted those of previous studies showing BR to be affected by decreases in PSA levels after radiation doses reached and exceeded 45 Gy [ 5 , 12 , 13 , 20 ]. In fact, our results revealed no evidence of BR in patients in whom PSA levels declined relatively early after the initiation of RT.…”
Section: Discussionsupporting
confidence: 92%
“…Despite salvage RT being a widely adopted strategy, our literature search yielded only 9 articles [ 5 13 ] and one review [ 20 ] on changes in PSA levels during RT. All but one of these articles showed that such changes might be a factor impacting biochemical or clinical recurrence [ 5 – 8 , 10 13 ], while the other article described changes in PSA levels as not being a factor associated with recurrence [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that PSA changes measured during SRT can be used to predict treatment outcome. 24,[36][37][38][39] Our results shown that the combined analysis of the PSA_start In the PSA_start -diffPSA plane (Figure 1), the diffPSA_ threshold line (Equation 2 F I G U R E 2 In the PSA_start-diffPSA plane, the diffPSA_threshold line ideally splits patients with post-SRTBF (above the line) from patients without post-SRTBF (below the line): the location of a patient in the PSA plane identifies the probability of evolution of his biochemical state…”
Section: Discussionmentioning
confidence: 79%
“…Some authors have reported that PSA changes measured during SRT can be used to predict treatment outcome 24,36‐39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation